Promo Cashback Gopay Terhadap Minat Beli Bubble Drink (Studi Kasus : Yu Cha Indonesia, Pluit) - Dewi Ayu Kusumaningrum; Suci Sandi Wachyuni (STIE Pariwisata API Yogyakarta, 2020)
The most popular technological and communication development innovations today are electronic payments without cash. GOPAY from PT Karya Anak Bangsa (GO-JEK) is the most widely used electronic payment in Indonesia. Yu Cha Indonesia is working with GOPAY to advance its business. There is currently a 20% GOPAY cashback promotion to attract more consumers. This study aims to look at the effect of the promotion of GOPAY (cashback) on the interest in buying bubble drinks at Yu Cha Indonesia. This research uses quantitative methods by distributing questionnaires to 99 respondents. Statistical analysis such as validation test, reliability test, normality test, and hypothesis test have been used. Data validation shows that all data is valid. Reliability tests are also reliable because the coefficient scores exceed Cronbach 'Alpha. The results of the r-score analysis are 0.707 which means that the two variables have a strong relationship. The r-square result is 0.499 and it can be concluded that the GOPAY cashback promotion affects product quality by 49.9% and the rest is influenced by other factors not discussed in this study. The results of this study show the positive and significant effect of the GOPAY (cashback) promotion program on consumer buying interest. Based on research results, the GOPAY promotion program (cashback) has a 49.9% effect on consumer buying interest.